Good practice in social care for disabled adults and older people with severe and complex needs: evidence from a scoping review. (27th July 2013) - Gridley, Kate; Brooks, Jenni; Glendinning, Caroline
Abstract This article reports findings from a scoping review of the literature on good practice in social care for disabled adults and older people with severe and complex needs. Scoping reviews differ from systematic reviews, in that they aim to rapidly map relevant literature across an area of interest. This review formed part of a larger study to identify social care service models with characteristics desired by people with severe and complex needs and scope the evidence of effectiveness. Systematic database searches were conducted for literature published between January 1997 and February 2011 on good practice in UK social care services for three exemplar groups: young adults with life‐limiting conditions; adults who had suffered a brain injury or spinal injury and had severe or complex needs; and older people with dementia and complex needs. Five thousand and ninety‐eight potentially relevant records were identified through electronic searching and 51 by hand. Eighty‐six papers were selected for inclusion, from which 29 studies of specific services were identified. However, only four of these evaluated a service model against a comparison group and only six reported any evidence of costs. Thirty‐five papers advocated person‐centred support for people with complex needs, but no well‐supported evaluation evidence was found in favour of any particular approach to delivering this. The strongest evaluation evidence indicated the effectiveness of a multidisciplinary specialist team for young adults; intensive case management for older people with advanced dementia; a specialist social worker with a budget for domiciliary care working with psycho‐geriatric inpatients; and interprofessional training for community mental health professionals. The dearth of robust evaluation evidence identified through this review points to an urgent need for more rigorous evaluation of models of social care for disabled adults and older people with severe and complex needs.